Gaseous neurotransmitters and their role in anapyrexia - Branco, Luiz G. S.; Bicego, Kenia C. [UNESP]; Carnio, Evelin C.; Pittman, Quentin J. (My University, 2010)
Mammals keep their body temperature (Tb) relatively constant even under a wide range of ambient temperature variation. However, in some particular situations it may be beneficial to increase or to decrease Tb. For instance, under hypoxic conditions, a regulated drop in Tb (anapyrexia) takes place which has been reported to be crucial for survival in a number of different species. This review highlights major advances in the research about nitric oxide (NO) and carbon monoxide (CO-where data are relatively less abundant), before focusing on the role played by these gaseous neuromediators in thermoregulation, under the conditions of euthermia and anapyrexia. Available data are consistent with the notion that both NO and CO, acting on the CNS, participate in thermoregulation, with NO decreasing Tb and CO increasing it. However further studies are required before definitive conclusions can be made as to their physiological mechanisms of action.
Keywords: agents interacting with transmitter, hormone or drug receptors; heme oxygenase; nitric oxide; animal; gas; metabolism; physiology; rat; review; thermoregulation; Animals; Body Temperature Regulation; Gases; Heme Oxygenase (Decyclizing); Neurotransmitter Agents; Nitric Oxide; Rats